North East Frontier Agency Draft Fourth Five Year Plan December 1964 - Planning Commission (Planning Commission, 1964)
This Draft outline of the Fourth Five Year Plan has been prepared in the order of Rs. 19.90 crores. Times than this is almost two and half/more the outlay in the third Plan and aims at securing further improvement in the various fields of development activities already in operation in N.E.F.l. This Plan follows the pattern of the Third Plan and is based on the recommendation of the various forking Groups of the Planning Commission. The Divisional Committees formed for this purpose have also been consulted before preparation of the Plan. While formulating this Plan, the experience gained and the lessons learnt during the Chinese aggression have been taken into consideration, and becomes of the need and urgency to develop the border areas at a much faster pace on account of the across the Northern Borders, Who proposed outlay is nearer thrice the outlay of the Third Plan. Ii all other respects, all the directions and suggestions of the Planning Commission have boon taken into consideration in so far as they are unlivable to us.
Planning and Development Department North East Frontier Agency Shillong
Planning and Development Department North East Frontier Agency Shillong
Keywords: Engineering; Roads; Airstrip; Power; Physical Targets under Engineering; Staff proposal under Engineering; Community Development; Publicity; Research; Statistics; General Introduction Indicating Broadly; Irrigation and Power; Problems and Proposals To Overcome Those Problems; Engineering Department